2007
DOI: 10.1124/jpet.106.116921
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase 1/2-Mediated Transcriptional Regulation of G-Protein-Coupled Receptor Kinase 3 Expression in Neuronal Cells

Abstract: Relatively small changes in G-protein-coupled receptor kinase (GRK) 3 expression (ϳ2-fold) profoundly affect ␣ 2 -adrenergic receptor (AR) function and preferentially regulate neuronal ␣ 2A -and ␣ 2B -AR signaling. In the present study, we provide evidence that epinephrine (EPI)-induced up-regulation of GRK3 protein expression in two neuronal cell lines, BE(2)-C cells (endogenously express ␣ 2A -and ␤ 2 -AR) and BN17 cells [endogenously express ␣ 2B (NG108) and transfected to express ␤ 2 -AR] is due in part to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Increased ERK1/2 levels can have a range of cellular effects. One particular study demonstrated the involvement of the ERK1/2 pathway in the upregulation of GRKs, via activation of Sp-1 and Ap-2 transcription factors in neuronal cells [55]. Increased arrestin-3 levels could also promote formation of another key scaffold complex, involving dephosphorylation and activation of Akt using PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ERK1/2 levels can have a range of cellular effects. One particular study demonstrated the involvement of the ERK1/2 pathway in the upregulation of GRKs, via activation of Sp-1 and Ap-2 transcription factors in neuronal cells [55]. Increased arrestin-3 levels could also promote formation of another key scaffold complex, involving dephosphorylation and activation of Akt using PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid turnover of GRK2 is consistent with high mRNA : protein ratio observed in this work. Stimulation of alpha2‐ and beta2‐ adrenoreceptors is reported to up‐regulates GRK3 in neuronal cell lines in an ERK1/2‐dependent manner, possibly, via activation of Sp‐1 and Ap‐2 transcription factors (Salim et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of GPCR antagonists or removal of endogenous agonists also can affect the GRK concentration (Hurle, 2001; Diaz et al, 2002; Bezard et al, 2005; Ahmed et al, 2007; Ahmed et al, 2008; Ahmed et al, 2010). The concentration of GRKs in vivo and in cultured cells is responsive to various conditions such as stress (Taneja et al, 2011), neonatal ventral hippocampal lesion (Bychkov et al, 2010), cell cycle progression (Penela et al, 2010), and drug treatment (Salim et al, 2007). Human diseases alter GRK levels.…”
Section: Grk Regulationmentioning
confidence: 99%
“…Epinephrine acting simultaneously via α 2 - and β2ARs upregulates the level of GRK3 mRNA and protein in neuronal cell lines (Salim et al, 2007). The action of epinephrine is mediated by the activation of ERK1/2 and possibly transcription factors Sp-1 and Ap-2.…”
Section: Grk Regulationmentioning
confidence: 99%